Career Adaptability And Career Anxiety In Job-Seeking Individuals With Disabilities: The Mediating Role Of Future Time Perspective - Kevin Wijaya; Barkah Barkah; Arman Jaya; Titik Rosnani; Efa Irdhayanti (Jurnal Mantik, 2026)
This study examined the relationship between career adaptability and career anxiety among job-seeking individuals with disabilities in Indonesia and tested the mediating role of Future Time Perspective (FTP) within the frameworks of Career Construction Theory and Social Cognitive Career Theory. Survey data from 120 respondents were analyzed using Partial Least Squares Structural Equation Modeling. Results show that career adaptability significantly reduces career anxiety and strongly predicts FTP. However, FTP neither predicts career anxiety nor mediates the relationship between adaptability and anxiety. These findings suggest that under structural labor-market constraints, adaptability functions primarily as a direct self-regulatory resource rather than through future-oriented cognition. The study highlights contextual limits of temporal cognition models and underscores the importance of strengthening adaptability in career interventions for individuals with disabilities